Հայ վաճառականութիւնն Իրաքի մէջ 17–19րդ դարերուն - Օհանեան, Սեդա (ՀՀ ԳԱԱ Պատմության ինստիտուտ)
Though Armenian trade community present in Mesopotamia during centuries, nevertheless its role was most dominant in the 17th and 18th centuries. Несмотря на то, что в Месопотамии армянское купечество имело на протяжении веков, но значимую роль сыграла в 17-ом и особенно в 18-ом веке.
Keywords: Հայոց պատմություն; Վաճառականություն; Հայ գաղթականություն; Իրաք